Attachment of Porphyromonas gingivalis to Corroded Commercially Pure Titanium and Titanium‐Aluminum‐Vanadium Alloy. Issue 9 (1st September 2014) - Barão, Valentim A.R.; Yoon, Cheon Joo; Mathew, Mathew T.; Yuan, Judy Chia‐Chun; Wu, Christine D.; Sukotjo, Cortino
Abstract : Background: Titanium dental material can become corroded because of electrochemical interaction in the oral environment. The corrosion process may result in surface modification. It was hypothesized that a titanium surface modified by corrosion may enhance the attachment of periodontal pathogens. This study evaluates the effects of corroded titanium surfaces on the attachment of Porphyromonas gingivalis. Methods: Commercially pure titanium (cp‐Ti) and titanium‐aluminum‐vanadium alloy (Ti‐6Al‐4V) disks were used. Disks were anodically polarized in a standard three‐electrode setting in a simulated oral environment with artificial saliva at pH levels of 3.0, 6.5, or 9.0. Non‐corroded disks were used as controls. Surface roughness was measured before and after corrosion. Disks were inoculated with P. gingivalis and incubated anaerobically at 37°C. After 6 hours, the disks with attached P. gingivalis were stained with crystal violet, and attachment was expressed based on dye absorption at optical density of 550 nm. All assays were performed independently three times in triplicate. Data were analyzed by two‐way analysis of variance, the Tukey honestly significant difference test, t test, and Pearson's correlation test (α = 0.05). Results: Both cp‐Ti and Ti‐6Al‐4V alloy‐corroded disks promoted significantly more bacterial attachment (11.02% and 41.78%, respectively; P <0.0001) than did the non‐corroded controls. Significantly more (11.8%) P. gingivalis attached to the cp‐Ti disks than to the Ti‐6Al‐4V alloy disks ( P <0.05). No significant difference in P. gingivalis attachment was noted among the corroded groups for both cp‐Ti and Ti‐6Al‐4V alloy ( P >0.05). There was no significant correlation between surface roughness and P. gingivalis attachment. Conclusion: A higher degree of corrosion on the titanium surface may promote increased bacterial attachment by oral pathogens.